National issues in the USA in economic development, mobility and income inequality - Alan E. Pisarski (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2016)
This assessment of the present context for evolving socio-economic patterns and trends in the United States is intended to support consideration of prospects for gains in income shares among the lower income population, recognising that the United States is: a very large heterogeneous population; highly dispersed over a large geographic area; highly technologically developed; and with relatively high incomes by world standards. All of these factors conduce to the need to recognize the characteristics of individual nations as they move toward improved incomes for their populations. The key factor for the future in the US will be better utilisation of the underemployed population to abet the need for skilled workers to support a large aging dependent population, including better education, and greater mobility providing access to employment and to other social and economic opportunities. It is hoped that this assessment adds further dimension to the important challenges addressed here.
Keywords: 330; Einkommensverteilung; Niedrigeinkommen; Arbeitslosigkeit; Soziale Integration; Soziale Mobilität; Mobilität; Wirtschaftswachstum; USA